A Multi-Sectoral Approach Improves Early Child Development in a Disadvantaged Community in Peru: Role of Community Gardens, Nutrition Workshops and Enhanced Caregiver-Child Interaction: Project “Wawa Illari” - González-Fernández, Doris; Mazzini Salom, Ana Sofía; Herrera Bendezu, Fermina; Huamán, Sonia; Rojas Hernández, Bertha; Pevec, Illène; Galarza Izquierdo, Eliana Mariana; Armstrong, Nicoletta; Thomas, Virginia; Vela Gonzáles, Sonia; Gonzáles Saravia, Carlos; Scott, Marilyn E.; et al. (Frontiers in Public Health, 2020)
Background: Multi-dimensional monitoring evaluation and learning strategies are needed to address the complex set of factors that affect early child development in marginalized populations, but few studies have explored their effectiveness. Objective: To compare improvement of health and development of children 0–3 years between intervention communities (IC) and control communities (CC) from peripheral settlements of Lima. Sequential interventions included: (1) home and community gardens, (2) conscious nutrition, and (3) parenting workshops following the International Child Development Program (ICDP). Methods: Interventions were delivered by community health promoters (CHPs) using a “step-by-step” learning system. Both IC and CC were monitored before the interventions began, at 8 and 12 months (n = 113 IC and 127 CC children). Data were collected on household characteristics, diet, food security, health indicators (history of diarrhea and respiratory infections, hemoglobin, intestinal parasites, anthropometry), caregiver-child interactions and stress, and achievement of Pan-American Health Organization age-specific developmental milestones. Stepwise multiple logistic regressions were used to determine if the interventions affected food insecurity, as well as motor, social/cognitive and language delays. Results: At baseline, 2.6% were categorized as “suspected developmental delay” and 14.2% were on “alert for development delay.” Food insecurity, diarrhea and respiratory infections were lowered following the interventions. Through the “step-by-step” approach, caregivers in IC gained skills in gardening, conscious nutrition and parenting that reduced the risk of food insecurity [Adjusted Risk Ratio = 0.20 (95% CI: 0.08–0.51)] and language delay [0.39 (0.19–0.82)] but not motor or social/cognitive delay. Use of a multiple micronutrient supplement decreased the risk of motor delay [0.12 (0.03–0.56)], but more pets were associated with higher risk of motor [3.24 (1.47–7.14)] and social/cognitive delay [2.72 (1.33–5.55)], and of food insecurity [1.73 (1.13–2.66)]. Conclusion: The combined interventions delivered by CHPs helped to mitigate the impact of adversity on food insecurity and language delay. Additional improvements may have been detected if the interventions had continued for a longer time. Our results indicate that control of infections and pets may be needed to achieve measurable results for motor and social/cognitive development. Continuous monitoring facilitated adjusting implementation strategies and achieving positive developmental outcomes.